Exploring value propositions and value drivers in task oriented information intensive online communities : case study - metal detecting find database - Huttu, Niko (2014)
Huttu, Niko Exploring Value Propositions and Value Drivers in Task Oriented Information Intensive Online Communities: Case Study - Metal Detecting Find Database Jyväskylä: Jyväskylän yliopisto, 2014, 166 s. Tietojärjestelmätiede, pro gradu –tutkielma Ohjaaja(t): Tuunanen, Tuure